Odpowiedzi

2010-03-25T16:47:56+01:00
A) 4x-3=3x+5 /-3x +3
x = 8

b) 5x+2=7-3x /+3x -2
8x = 5 /:8
x = 5/8

c) 3(x-1)=0
3x-3 = 0 /+3
3x = 3 /:3
x = 1

d) -6(x+1)=24
-6x-6 = 24 /+6
-6x = 30 /:(-6)
x = -5
2010-03-25T16:48:31+01:00
A) 4x-3=3x+5
4x-3x=5+3
x=8

b) 5x+2=7-3x
5x+3x=7-2
8x=5 /:8
x=5/8

c) 3(x-1)=0
3x-3=0
3x=3 /:3
x=1

d) -6(x+1)=24
-6x -6=24
-6x=24+6
-6x=30 /:(-6)
x=-5
2010-03-25T16:48:55+01:00
A) 4x-3=3x+5
4x - 3x = 5 + 3
x = 8
b) 5x+2=7-3x
5x + 3x = 7-2
8x = 5 /:8
x = 5/8
c) 3(x-1)=0
3x - 3 = 0
3x = 3 / :3
x = 1
d) -6(x+1)=24
-6x - 6 = 24
-6x = 24 +6
-6x = 30 /: (-6)
x = -5